Cervical length screening as a predictor of spontaneous preterm birth in low risk singleton pregnancy - Nadia Ramli (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Preterm birth is the most common cause of perinatal mortality and morbidity. Although the survival rate has improved, the surviving neonate carries risk of long term neurological impairment, respiratory and gastrointestinal problems. Two third of preterm birth are spontaneous. Various prediction methods of preterm birth were found to have limited predictive ability. Transvaginal cervical length measurement is a safe and gold standard method. Cervical length screening in high risk patient was recommended, however limited scientific evidence in universal cervical length screening for a low risk women. This research is aim to predict spontaneous preterm birth in singleton pregnancies of low risk primigravida through their cervical length measurement. This is a prospective observational study in 380 primigravidae. Pregnant mothers between 18 to 24+6 weeks gestation were recruited and cervical length (CL) screening done by transvaginal ultrasound. They were followed up until delivery. 380 primigravida were screened and 4.8% were delivered preterm (<37 weeks) of which only 0.5 % had cervical length of < 2.5 cm. Further statistical analysis found that 2.6% of total recorded deliveries were preterm birth with cervical length < 3.5cm and the mode is 3.1cm. Cervical length < 3.5cm between 18 to 24 + 6 weeks gestation, gives a positive predictive value of 37% and negative predictive value of 98%. Based on ROC curve, cervical length is a good predictive tool to predict term delivery in a low risk population. From the study it shows that cervical length < 2.5cm carries risk of preterm birth. However the percentage of short cervical length is very small and it would not be a feasible screening method due to limited resources in our health care centre. Further study with larger sample size should be conducted to focus on cervical length < 3.5cm to predict preterm birth.